2019
DOI: 10.1002/pen.25127
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the reinforcing efficiency of waste eggshell‐derived nano calcium carbonate in natural rubber composites with maleated natural rubber as compatibilizer

Abstract: Calcium carbonate nanoparticles were synthesized from eggshell waste using ball mill treatment and characterized by Fourier transform infrared (FTIR), X‐ray diffraction (XRD), and field‐emission scanning electron microscopy (FESEM) analysis. Then, waste eggshell‐derived nano calcium carbonate (WESNCC) was used as filler to reinforce natural rubber (NR) composites with and without the presence of maleated natural rubber (MNR) as compatibilizer. MNR‐compatibilized NR/WESNCC composites showed remarkable enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…[14,15] The grafting reaction via reactive melt mixing in the melt phase using an extruder or internal mixer has been developed by many researchers for grafting MA onto polyolefin [16][17][18][19][20][21][22][23][24] and NR. [25][26][27] The grafting copolymerization of MA onto the NR molecules has generally been performed in the molten state using peroxide or the shearing action of the materials in machines as initiators. Therefore, this process is environment-friendly way because it only uses the polymer backbone and a new functional group monomer (and initiator), which is claimed to reduce or minimize the harm upon the environment, while other processes require more solvents (solution polymerization), emulsifiers (emulsion polymerization), initiators, and other additives.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] The grafting reaction via reactive melt mixing in the melt phase using an extruder or internal mixer has been developed by many researchers for grafting MA onto polyolefin [16][17][18][19][20][21][22][23][24] and NR. [25][26][27] The grafting copolymerization of MA onto the NR molecules has generally been performed in the molten state using peroxide or the shearing action of the materials in machines as initiators. Therefore, this process is environment-friendly way because it only uses the polymer backbone and a new functional group monomer (and initiator), which is claimed to reduce or minimize the harm upon the environment, while other processes require more solvents (solution polymerization), emulsifiers (emulsion polymerization), initiators, and other additives.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast the tan δ value of SE 87:5 12:5 À gSRP 30 200 was higher than that of SE 87:5 12:5 À gSRP 0 200 (Figure 7B). Moreover, the hysteresis loop of SE 87: 5 12:5 À gSRP…”
Section: Morphology and Performance Of Rubber Compositesmentioning
confidence: 99%
“…Roy et al used waste‐eggshell‐derived nano calcium carbonate as the reinforcer to enhance the mechanical properties of natural rubber. [ 5 ] Moreover, their research team used gypsum waste from the ceramic industry as a semi‐reinforcing filler for epoxidized natural rubber and demonstrated that the reinforcement efficiency of gypsum waste was higher than that of commercially available calcium carbonate. [ 6 ] Silicone‐based composite insulators (SCIs) are widely used in outdoor high‐tension transmission lines because of their high specific intensity and excellent wet‐moisture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Salah satu sumber CaCO3 adalah kulit telur yang merupakan limbah yang terus meningkat setiap tahunnya dan menjadi salah satu limbah rumah tangga terbanyak di Indonesia dan di dunia. 13,14 Penggunaan kalsium karbonat dari kulit telur dapat mengatasi permasalahan limbah kulit telur sekaligus menjadi alternatif dalam menurunkan hormon paratiroid untuk mengatasi penyakit secondary hyperparathyroidism. 9,[15][16][17] Artikel ini diharapkan dapat memberi kontribusi mengenai modalitas yang baru berupa ekstrak kulit telur yang dapat menjadi terapi hiperparatiroid sekunder yang disebabkan oleh PGK pada masa mendatang.…”
Section: Pendahuluanunclassified
“…Komponen utama dari kulit telur adalah CaCO3 dimana terdapat sebanyak 94%-97% kadar kalsium karbonat dalam kulit 1 butir telur, yang setara dengan 1,5 gram kalsium. 13,22,23 Selain itu terdapat juga fosfor dan magnesium, dan sejumlah kecil natrium, kalium, seng, mangan, besi, dan tembaga. 15,24,25 Kulit telur dapat berasal dari bermacam hewan seperti ayam dan bebek.…”
Section: Gambaran Umum Dan Kandungan Kulit Telur (Gallus Domesticus)unclassified